Channel and Marketing Efficiency Analysis of Shallot in East Lombok Regency - Muhammad Nursan; M. Yusuf; Syarif Husni; Nurtaji Wathoni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Shallot is one of the most consumed horticultural products by the public. Shallot consumption continues to increase, so marketing factors must be a priority to pay attention to so that these products can reach consumers. The purpose of this study was to analyze the channels, functions, margins, and marketing efficiency of shallots in the Sembalun District, East Lombok Regency. This study uses a qualitative and quantitative research method (Mixed method). Data were collected by conducting a questionnaire survey of 30 respondents determined by quota sampling and marketing agency respondents determined by snowball sampling and data analysis conducted descriptively. From the results of the analysis, it was found that there were 3 marketing channels for shallots in East Lombok Regency. Marketing functions carried out by shallot marketing actors or agencies include all marketing functions except processing and standardization functions. The shallot marketing margin in channel 1 is IDR 3,200 per kilogram, lower than the marketing margin in channel 2, which is IDR 6,000 per kilogram, and channel 3, which is IDR 8,000 per kilogram. Marketing of shallots in East Lombok Regency is classified as efficient because the value of farmer participation in the three marketing channels is > 50%